Adaptation and Returns from Improved Indigenous Small Ruminants in Climatically Challenged Smallholder Systems of Kenya - Sila, Winfred; Gachuiri, Charles K; Recha, John W.M.; Audho, James; Ojango, Julie M.K. (MDPI, 2021)
Improved climate-resilient strains of indigenous sheep and goats were introduced in the Nyando basin of western Kenya in 2013. This study evaluated the performance of the breeds five years after their first introduction and their contribution to household revenues. Red Maasai and Red Maasai x Dorper sheep and Galla goats introduced in Nyando adapted to the environment and retained performance levels exhibited in their original environments. They have been widely adopted by the farmers and are used for upgrading local breeds through crossbreeding, yielding offspring that are 50% heavier than local breeds at one year of age. Costs for producing the small ruminants tend to increase with land size owned, mainly due to higher costs for managing the health of more livestock. The costs of producing goats are significantly higher than for sheep. Revenues accrued from goat milk contribute to 10% of the revenue from goats. The introduced breeds provided a significant productivity lift in the local livestock population, resulting in higher returns to the smallholder farmers. For long-term sustainability of the productivity gains, a community-based selective mating program using reference sire flocks with an overall goal of good growth, adaptability, and milk production should be adopted.